THE FIRST PALEOSEISMIC TRENCH DATA FROM ACIPAYAM FAULT, FETHİYE BURDUR FAULT ZONE, SW TURKEY - Kürçer, A.; Özdemir, E.; Uygun Güldoğan, Ç.; Duman, T.Y. (Bulletin of the Geological Society of Greece, 2016)
The Acıpayam Fault is an active fault segment which is located on the central part of Fethiye Burdur Fault Zone in SW Turkey. According to the Active Fault Map of Turkey published by MTA (Turkey), it is described as a Quaternary fault. Acıpayam Fault extends from Acıpayam at northeast to Akköprü Dam at southwest. The general strike of fault is N 35°E, approximately 60 km long and it’s a normal fault with minor sinistral strike-slip component. The fault is composed of three fault section, which are named as Örenköy, Olukbaşı and Yolçatı, seperated from each other by step-over zones. In this study, active tectonic features of Acıpayam fault are investigated and paleoismological trench surveys are perfomed at the Örenköy fault section. Two cross trenches were excavated along the fault. The samples collected from the trenches were dated using the 14C dating method. Örenköy trenches were photographed using the Paleoseismological Three Dimensional Virtual Photography Method, which is a new tecnique for paleoseismology. According to the trench microstratigraphy, structural data and dating results, Acıpayam fault is described as a Holocene fault. The date of last event that occurred on the Acıpayam fault is between 3030 ± 30 BP and 2410 ± 30 BP.